PDLIM7 Synergizes With PDLIM2 and p62/Sqstm1 to Inhibit Inflammatory Signaling by Promoting Degradation of the p65 Subunit of NF-κB - Jodo, Aya; Shibazaki, Azusa; Onuma, Asuka; Kaisho, Tsuneyasu; Tanaka, Takashi (Frontiers in Immunology, 2020)
Activation of NF-κB transcription factors is critical for innate immune cells to induce inflammation and fight against microbial pathogens. On the other hand, the excessive and prolonged activation of NF-κB causes massive inflammatory damage to the host, suggesting that regulatory mechanisms to promptly terminate NF-κB activation are important to prevent immunopathology. We have previously reported that PDLIM2, a PDZ-LIM domain-containing protein, is a nuclear ubiquitin E3 ligase that targets the p65 subunit of NF-κB for degradation, thereby suppressing NF-κB activation. Here we show that PDLIM7, another member of LIM protein family, is also a ubiquitin E3 ligase that inhibits NF-κB-mediated inflammatory responses. PDLIM7 directly polyubiquitinates p65 and promotes its proteasomal degradation. Moreover, PDLIM7 heterodimerizes with PDLIM2 to promote synergistic PDLIM2-mediated degradation of p65. Mechanistically, PDLIM7 promotes K63-linked ubiquitination of PDLIM2 and then the proteasome/ autophagosome cargo protein p62/Sqstm1 binds to both polyubiquitinated PDLIM2 and the proteasome, thereby facilitating the delivery of the NF-κB-PDLIM2 complex to the proteasome and subsequent p65 degradation. Consistently, double knockdown of PDLIM7 and either PDLIM2 or p62/Sqstm1 results in augmented proinflammatory cytokine production compared to control cells or single knockdown cells. These data delineate a new role for PDLIM7 and p62/Sqstm1 in the regulation of NF-κB signaling by bridging a ubiquitin E3 ligase and the proteasome.